2016
DOI: 10.1039/c6ra01906d
|View full text |Cite
|
Sign up to set email alerts
|

Nano-cuprous oxide catalyzed one-pot synthesis of a carbazole-based STAT3 inhibitor: a facile approach via intramolecular C–N bond formation reactions

Abstract: In this study, we report the one-pot synthesis of substituted carbazole derivatives using nano cuprous oxide as a catalyst via intramolecular C-N bond forming reactions. Among the synthesized carbazoles, 3'-((3-acetyl-6-chloro-9H-carbazol-9-yl)methyl)-[1,1'-biphenyl]-2-carbonitrile (ACB) was identified as lead antiproliferative agent against lung cancer cell lines A549 and LLC with an IC 50 of 13.6 and 16.4 µM respectively. Further, we found that lead compound suppresses the constitutive phosphorylation of STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…EMT can be modulated by diverse transcription factors including zinc-finger E-box-binding (ZEB), Twist, Snail, and Slug [16] , [17] , [18] . STAT3 is frequently overactivated in different tumors including hepatocellular carcinoma (HCC) and can positively correlate with tumorigenicity, EMT, antiapoptosis, and metastasis [19] , [20] , [21] , [22] . IL-6 activates STAT3 to promote EMT through the induction of Snail expression in cancers [8] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…EMT can be modulated by diverse transcription factors including zinc-finger E-box-binding (ZEB), Twist, Snail, and Slug [16] , [17] , [18] . STAT3 is frequently overactivated in different tumors including hepatocellular carcinoma (HCC) and can positively correlate with tumorigenicity, EMT, antiapoptosis, and metastasis [19] , [20] , [21] , [22] . IL-6 activates STAT3 to promote EMT through the induction of Snail expression in cancers [8] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…2-ethoxy-4,5-diphenyl-1,3-oxazine-6-one is a small molecule reported to decrease the levels of nuclear NF-κB in lipopolysaccharide (LPS)-induced NGF-differentiated PC12 cells [ 16 ]. Given the relevance with aforementioned reports and in continuation of our effort to synthesize various heterocycles to explore their medicinal properties [ 17 24 ], herein we prepared the series of oxazine derivatives and evaluated their effect on HCT116 cells. The lead compounds 2-((2-acetyl-6,6-dimethyl-4-phenyl-5,6-dihydro-2H-1,2-oxazin-3-yl)methyl)isoindoline-1,3-dione (API) and dimethyl 2-((2-acetyl-4-(4-methoxyphenyl)-6,6-dimethyl-5,6-dihydro-2H-1,2-oxazin-3-yl)methyl)malonate (DMO) were chosen and evaluated for their NF-κB DNA binding inhibitory activity and NF-κB dependent luciferase expression studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have demonstrated the persistent phosphorylation of STAT3 in 22-65% of NSCLC [81], and the deregulation of STAT3 has been associated with malignant transformation [86,87]. The phosphorylation of Tyr705 is a critical event in regulating the transcriptional activity of STAT3, and mitigation of phosphorylation can result in a decline in the STAT3 nuclear pool [88]. Therefore, blocking of nuclear translocation of STAT3 by inhibiting its phosphorylation could be a therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%